Effects of inherent alkali and alkaline earth metallic species on biomass pyrolysis at different temperatures. (September 2015) - Hu, Song; Jiang, Long; Wang, Yi; Su, Sheng; Sun, Lushi; Xu, Boyang; He, Limo; Xiang, Jun
Highlights: Inherent AAEMs affected distribution of pyrolysis product at different temperatures. Water–gas shift reaction was enhanced by inherent AAEMs. Decomposition of levoglucosan was accelerated significantly by inherent AAEMs. Breakage and restructuring of hetero atoms of tar were promoted by inherent AAEMs. Abstract: This work aimed to investigate effects of inherent alkali and alkaline earth metallic species (AAEMs) on biomass pyrolysis at different temperatures. The yield of CO, H2 and C2 H4 was increased and that of CO2 was suppressed with increasing temperature. Increasing temperature could also promote depolymerization and aromatization reactions of active tars, forming heavier polycyclic aromatic hydrocarbons, leading to decrease of tar yields and species diversity. Diverse performance of inherent AAEMs at different temperatures significantly affected the distribution of pyrolysis products. The presence of inherent AAEMs promoted water–gas shift reaction, and enhanced the yield of H2 and CO2 . Additionally, inherent AAEMs not only promoted breakage and decarboxylation/decarbonylation reaction of thermally labile hetero atoms of the tar but also enhanced thermal decomposing of heavier aromatics. Inherent AAEMs could also significantly enhance the decomposition of levoglucosan, and alkaline earth metals showed greater effect than alkali metals.